Agile Processes in Software Engineering and Extreme Programming 10th International Conference, XP 2009, Pula, Sardinia, Italy, May 25-29, 2009, Proceedings - Abrahamsson, Pekka; Marchesi, Michele; Maurer, Frank (Lecture Notes in Business Information Processing, 2009)
The field of software engineering is characterized by speed and turbulence in many regards. While new ideas are proposed almost on a yearly basis, very few of them live for a decade or a longer. Lightweight software development methods were a new idea in the latter part of the 1990s. Now, ten years later, they are better known as agile software development methods, and an active community driven by practitioners has formed around the new way of thinking. Agile software development is currently being embraced by the research community as well. As a sign of increased research activity, most research-oriented conferences have an agile software development track included in the conference program. The XP conference series established in 2000 was the first conference dedicated to agile processes in software engineering. The idea of the conference is to offer a unique setting for advancing the state of the art in research and practice of agile processes. This year's conference was the tenth consecutive edition of this international event. Due to the diverse nature of different activities during the conference, XP is claimed to be more of an experience rather then a regular conference. It offers several different ways to interact and strives to create a truly collaborative environment where new ideas and exciting findings can be presented and shared. This is clearly visible from this year's program as well.